3D digital image correlation evaluation of arthrodesis implants. (January 2020) - Shen, Victor ChuYu; Bumgardner, Clifton H.; Actis, Lisa; Ritz, Joseph; Park, Joseph; Li, Xiaodong
Abstract: Background: Hallux valgus is a pathological condition that is typically treated via the Lapidus procedure. The purpose of this study was to understand the biomechanical characteristics of bone, implant devices and the bone-implant interface. Methods: In-situ digital image correlation was performed on polyurethane foam, a known bone substitute in a modified three-point bend test frame. We introduced this modified rig as an enhanced methodology for characterizing bone and implant device mechanical performance. This new methodology was validated using aluminum rod specimens, in three and four-point bend setups followed by new configurations to reveal implications of load configurations on joint displacement and implant performance. Bone substitute specimens were constructed with nitinol staples or locking plate to minimize gapping at the 1 st tarsometatarsal during testing. Findings: Bone-implant interface characterization was enabled by digital image correlation, identifying maximum strain concentrations of 1.5% along the interfaces. Interfacial characteristics were analyzed in context with gap displacement allowed by the implant over cyclical loading. The locking plate implant and nitinol staples gapped an average of 2.2 mm and 3.2 mm respectively under 50 Newtons. Removing all load, the locking plate implant and nitinol staples averaged ~0.8 mm and ~0.3 mm of residual gapping respectively. Interpretation: Our results demonstrate that locking plates provide more initial stability and resistance against gapping under load but are unable to recover compression throughout repetitive loading as seen with the nitinol staple technology. This could lead to a paradigm shift in materials used for early weight bearing protocols post-operation. Highlights: Lapidus procedures lacks standardization when identifying causes of non-union. Introduced new asymmetric bend test methodology for accurate loading of the bone Digital image correlation was used to characterize bone and implant performance. Locking plates provide superior initial stability but lose compression gradually. Nitinol staples exhibited extended compression but allow larger gapping.